Day Care Workers in the Prevention Process: A Study of Their Orientation to Children and Implications for Day Care Training - Shell, Nina J.; James, Susan (Canadian Journal of Counselling and Psychotherapy, 2012)
Prevention as a concept can be applied to a population closely associated with children: that of day care workers. This study outlines typical problems and concerns of workers as well as several important parameters of the day care work world. The implications of these variables for planning for and promoting children's mental health in day care settings are carefully examined.